Gaya Bahasa Sindiran Warganet di Kolom Komentar Akun Youtube @Thekufaku pada Konten “Cuma Kamu” - Nata, Rangga; Agustina, Agustina (Persona: Kajian Bahasa dan Sastra, 2024)
Language is a tool for communicating with others to convey one’s thoughts and feelings to the interlocutor. The communication process occurs not only in real life but also in the virtual world. The use of social media often involves distinctive styles or methods of conveying messages or information. Therefore, this study aims to (1) describe the types of sarcastic language and (2) describe the functions of sarcasm used by netizens in the comment section of the YouTube account @thekufaku on the content “Cuma Kamu.” This research is qualitative in nature, using a descriptive method. The data consists of sentences written by netizens in the comment section of the YouTube account @thekufaku on the content “Cuma Kamu.” The data collection techniques used are observation, reading, and note-taking. The steps of data analysis in this study are: (1) identifying the collected data, (2) classifying the data based on the research objectives using a format, (3) analyzing the classified data, and (4) formulating conclusions from the analysis results. The findings of this study are as follows. First, 108 instances of sarcastic language were found in the comment section of the YouTube account @thekufaku on the content “Cuma Kamu,” consisting of: (1) 12 instances of sarcasm, (2) 17 instances of cynicism, (3) 18 instances of irony, (4) 49 instances of satire, and (5) 12 instances of innuendo. Second, the functions of sarcasm identified in this study include: (1) conveying specific intentions (42 instances), (2) criticizing (15 instances), (3) persuading/influencing (40 instances), and (4) advising (11 instances). Thus, the sarcastic language used by netizens in the comment section of the YouTube account @thekufaku on the content “Cuma Kamu” predominantly conveys sarcasm for specific purposes, mainly in the form of jokes mocking human weaknesses or mistakes.